Interactive effects of pH, temperature and exposure period on native and invasive mussels from the West Coast of South Africa - Emanuel, Martin Phillippe (Department of Biological Sciences, 2014)
Global warming and ocean acidification due to an increase in anthropogenic carbon dioxide can impact marine calcifying organisms. Shells of marine calcifying organisms protect their internal soft tissue and may be key in determining the susceptibility of marine calcifiers to these environmental stressors. To test this, the effects of pH, temperature, exposure period and their interactions on the performance of native and alien mussels with varying shell thickness was studied. Listed in order of decreasing shell thickness, I compared shell dissolution, shell growth, shell breaking force and condition index of Aulacomya ater, Choromytilus meridionalis (both native), Mytilus galloprovincialis and Semimytilus algosus (both invasive) found on the Western Cape coast of South Africa. Live mussels and bare shells were exposed to seawater temperatures of 14°C and 20°C set at two pH levels (7.5 and 8.0) for roughly 40 days. Live mussels were either exposed to aerial drying for four hours per day or fully submerged for the duration of the study. The results suggest that shell thickness determines the susceptibility of mussels to environmental stressors, in terms of shell dissolution and breaking force, but does not affect internal growth. Invasive mussels showed increased shell dissolution at low pH but their growth rates were unaffected. They also exhibited higher condition indices than native mussels under low pH and high temperatures. On the other hand, the thicker shelled native mussels showed no significant changes in shell dissolution among the treatments and exhibited increases in growth rates in low pH treatments. C. meridionalis, being cold water adapted, exhibited a reduction in condition index in high temperature treatments. The study indicates that native and invasive mussels have different compensatory mechanisms to respond to anthropogenic impacts. These mechanisms allow them to maintain their specific life history strategies under short term exposure to warming and acidification. It was also elucidated that mussels exposed to low temperature aerial conditions exhibit increased shell and tissue growth as periodic exposure minimises the deleterious effects of ocean acidification and warming. The findings suggest that native and invasive mussels respond differently to ocean acidification and warming depending on their specific physiologies and life history strategies.